Pre-existing risk factor profiles in users and non-users of hormone replacement therapy: prospective cohort study in Gothenburg, Sweden - Rödström, Kerstin (British Medical Journal, 1999)
OBJECTIVE: To assess whether risk factor profiles for cardiovascular disease differed, before starting treatment, between women who would subsequently use hormone replacement therapy and those who would remain untreated. DESIGN: Prospective population study, initiated in 1968-9, with follow ups in 1974, 1980, and 1992. SETTING: Gothenburg, Sweden. PARTICIPANTS: 1201 women born in 1918, 1922, and 1930, representative of women of the same age in the general population. MAIN OUTCOME MEASURES: Hormone replacement therapy as a function of initial systolic and diastolic blood pressure, waist and hip circumference, waist to hip ratio, body mass index, serum concentrations of cholesterol and triglycerides, smoking status, education, leisure time activity, and socioeconomic group. RESULTS: 179 of the 1202 women (14.9%) used hormone replacement therapy sometime during the 24 year follow up period. Multivariate models indicated that these women had significantly lower blood pressure, had less obesity, and belonged to a higher social group before the start of treatment than women who would remain untreated. CONCLUSION: Women who would subsequently use hormone replacement therapy were already at lower cardiovascular risk before the start of treatment than women who would remain untreated. Some of the claimed beneficial effects of treatment may thus be explained by women who would use hormone replacement therapy representing a healthier cohort than women who would remain untreated.